(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This investigation represents an experimental modal analysis of a non-uniform mild steel beam under clamped-free (C-F) boundary conditions. Non-uniform beams are commonly found in engineering applications, and their modal characteristics play a crucial role in design and performance optimization. The experimental modal analysis of a non-uniform clamped-free beam is performed with a laser vibrometer excited with impact hammer excitation. We describe the experimental setup, data acquisition, and signal processing techniques used to extract natural frequencies, mode shapes, and damping ratios. The excited wave signals are converted into the frequency domain and time domain by using FFT (Fast Fourier Transformation). The simulation is performed using COMSOL Multiphysics software 5.6 and ANSYS Workbench 18.1. Thus, the experimental natural frequency and mode shapes of the non-uniform beam are compared with simulation results. A comparison of results obtained experimentally shows a good validation with the results obtained from simulation. The obtained results be used as a reference for future investigation in this domain.